Early Neonatal Cyanosis as a Presentation of a Rare Cardiac Anomaly: Truncus Arteriosus Type IV - Amjad Mohamed Haider; Ammar M.H. Shehadeh; Rola Mohamed Alfarra (Dubai Medical Journal)
Truncus arteriosus (TA) is a rare congenital heart anomaly presenting with mild cyanosis and congestive heart failure. It occurs when the blood vessels coming out of the heart in the developing baby fail to separate completely during development, leaving a common trunk responsible for the pulmonary and systemic perfusion. There are several variants of TA, depending on the specific anatomy and arterial connection. We report a case of a full-term newborn who developed cyanosis and desaturation during the first day of life. Investigations and echocardiography were consistent with TA type IV. Prostaglandin infusion was immediately started, and then, a successful palliative right modified Blalock Taussig shunt was performed.